Error detection techniques applicable in an architecture framework and design methodology for autonomic SoCs - Bouajila, Abdelmajid (2006)
This work-in-progress paper surveys error detection techniques for transient, timing, permanent and logical errors in system-on-chip (SoC) design and discusses their applicability in the design of monitors for our Autonomic SoC architecture framework. These monitors will be needed to deliver necessary signals to achieve fault-tolerance, self-healing and self-calibration in our Autonomic SoC architecture. The framework combines the monitors with a welltailored design methodology that explores how the Autonomic SoC (ASoC) can cope with malfunctioning subcomponents.